Apoptosis and activation of the sphingomyelin-ceramide pathway induced by oxidized low density lipoproteins are not causally related in ECV-304 endothelial cells - Escargueil-Blanc, Isabelle; Andrieu-Abadie, Nathalie; Caspar-Bauguil, Sylvie; Brossmer, Reinhard; Levade, Thierry; Nègre-Salvayre, Anne; Salvayre, Robert (The journal of biological chemistry, 1998)
Oxidized low density lipoproteins (oxLDL) are thought to play a central role in the development of atherosclerosis. Toxic concentrations of mildly oxidized LDL elicit massive apoptosis of endothelial cells (Escargueil-Blanc, I., Meilhac, O., Pieraggi, M. T., Arnal J. F., Salvayre, R., Nègre-Salvayre, A. (1997)Arterioscler. Thromb. Vasc.Biol. 17, 331-339). Since the lipid mediator ceramide emerged as a potent inducer of apoptosis, we aimed at investigating the occurrence of ceramide formation and its potential role in oxLDL-induced apoptosis. In ECV-304 endothelial cells, toxic concentrations of oxLDL triggered an early activation of the sphingomyelin-ceramide pathway, as shown by both sphingomyelin hydrolysis and ceramide formation.N-Tosyl-l-phenylalanyl chloromethyl ketone (TPCK) and dichloroisocoumarin (DCIC), two serine-protease inhibitors (serpins), blocked the oxLDL-induced ceramide generation but, unexpectedly, did not inhibit the oxLDL-induced apoptosis. Conversely, treatment of endothelial cells by bacterial sphingomyelinase, under conditions effectively generating ceramide, did not induce apoptosis. In contrast, short-chain permeant C2- and C6-ceramides elicited apoptosis of ECV-304. However, the mechanisms of apoptosis triggered by C2-ceramide and by oxLDL were (at least in part) different, because C2-ceramide-induced apoptosis was calcium-independent, whereas oxLDL-induced apoptosis was calcium-dependent. In conclusion, it is suggested that oxLDL-induced apoptosis is calcium-dependent but independent of the activation of the sphingomyelin-ceramide pathway and that the toxic effect of short chain permeant ceramides is calcium-independent and does not mimic the effect of natural ceramides induced by oxLDL.
Artikel-Version: 4. Januar 2021
Gesehen am 27.06.2024